Analysis of the Growth Rate, Effectiveness, Potential, and Contribution of Advertising Tax to Local Original Income (PAD) in Mataram City 2019-2023 - Addini Nurizzati; Muthmainnah Milliani; Dwikora Harjo (Economy and Finance Enthusiastic, 2025)
This study analyzes the performance of Mataram City's advertising tax during 2019–2023 using a quantitative descriptive approach to assess the dynamics of growth rates, collection effectiveness, potential estimates, and its contribution to Regional Original Income (PAD). Secondary data are sourced from official local government documents (PAD and advertising tax target–realization), while measurements use standard measures: annual growth (current year realization compared to the previous year), effectiveness (ratio of realization to target), potential, and contribution (ratio of advertising tax realization to PAD realization). The results show an average growth rate of 56.28% (categorized as quite successful) with high volatility: a contraction in 2020 due to the pandemic shock and a sharp decline in 2023 related to the regulation of bando, changes in the stock of high-value objects, and compliance friction. The average collection effectiveness is 93.39% (effective), but is sensitive to target setting, especially during policy revisions or changes. The estimated average annual revenue of Rp468,394,100.00 is relatively small compared to the object-based revenue and historical realizations, indicating the need to standardize time units and the tax base for each media type to ensure more representative rental values. The average contribution of advertising tax to local revenue (PAD) is 1.08%, which is relatively low. Therefore, this channel is more appropriately positioned as a stable source of additional revenue if inventory management, licensing, electronic billing, and compliance enforcement are strengthened.